Volatility and Growth in Latin America An Episodic Approach - Sahay, Ratna (International Monetary Fund, 2006)
This paper compares the pattern of macroeconomic volatility in 17 Latin American countries during episodes of high and low growth since 1970, examining in particular the role of policy volatility. Macroeconomic outcomes are distinguished from macroeconomic policies, structural reforms and reversals, shocks, and institutional constraints. Based on previous work, a composite measure of structural reforms is constructed for the 1970-2004 period. We find that outcomes and policies are more volatile in low growth episodes, while shocks (except U.S. interest rates) are similar across episodes. Fiscal policy volatility is associated with lower growth, but fiscal policy procyclicality is not. Low levels of market-oriented reforms and structural reform reversals are also associated with lower growth